Finding Thoreau in French Canada: The Ideological Legacy of the American Revolution. Issue 3 (3rd July 2017) - Lacroix, Patrick
ABSTRACT: Henry David Thoreau's Yankee in Canada is easily overlooked. Because it is so selective in its depiction of life in the St. Lawrence River valley, historians of mid-nineteenth-century Canada have shown little interest in Thoreau's first-hand account. To American readers, it offers little of the characteristic Thoreau found in Walden and Resistance to Civil Government . Yet, it is highly significant as an expression of national self-definition. Thoreau borrowed themes at least as old as the American Revolution when noting the pernicious rule of Catholic and British power in Canada. He set out to expose the promise of republican values by emphasizing the contrast between these and the poor and morally stunted life under Old World institutions. His work must therefore be interpreted as a call to his audience to commit more deeply than ever to the ideals that animated the Great Republic's founding moment. It must also stand as a civic interpretation of American nationality at a time when this perspective was waning. Before long, Old World peoples would be racialized and the ideological embrace of the republican values advanced by Thoreau would no longer suffice in making American citizens.